USING E-LEARNING MODEL ON STUDENTS’ WRITING OF DESCRIPTIVE TEXTS (Jurnal Pelangi : Research of Education and Development, 2016)
E-learning refers to electronic learning using technology devices as a learning media to motivate and sharpen students’ writing skill. The purpose of the research is to obtain empirical data about whether or not the effects of using e-learning model on students’ writing of descriptive texts. The research was conducted at SMK An-Nuqthah Tangerang of class X in the second semester of 2015-2016 academic year. Research method was experiment by using e-learning model in the first class and without e-learning (conventional model) in the second class with 25 participants of each class. The data were taken from students’ descriptive texts. The results showed that the highest score in the experimental class was 94 while the lowest one was 66.  In addition, the highest score in the control class was 86 whereas the lowest one was 60. It was found that the value of tobtained was higher than the value of ttable (3.08 > 2.01) with df = 48 and a = 0.05. Since H1 was accepted, it proved that there was a significant difference of using e-learning model on students’ writing of descriptive texts